The effect of molecular structure of chlorin photosensitizers on photo-bleaching of 1,3-diphenylisobenzofuran—the possible evidence of iodine reactive species formation - Kustov, Andrey; Morshnev, Philipp; Kukushkina, Natal’ya; Krestyaninov, Mikhail; Smirnova, Nataliya; Berezin, Dmitry; Kokurina, Galina; Belykh, Dmitry (Comptes Rendus. Chimie)
In this short communication, we focus on the ability of chlorin e$_{6}$ photosensitizers (PSs) with one, two or three cationic groups to generate singlet oxygen species ($^{1}$O$_{2}$) in an apolar model medium, viz. 1-octanol (OctOH). The quantum yield of $^{1}$O$_{2}$ ($Φ _{Δ }$) is determined indirectly by the chemical method for seven synthesized PSs using 1,3-diphenylisobenzofuran (DPBF) as a singlet oxygen trap. The $Φ _{Δ }$ values of four PSs with one or two cationic groups occupying opposite positions in the macrocycle are equal to 0.6, which is nearly identical to the values obtained by the time-resolved fluorescence spectroscopy method. In contrast, three PSs containing a 3(1),3(2)-bis-(N,N,N-trimethylaminomethylvinyl) iodide fragment with two adjacent cationic groups have an abnormally high quantum yield reaching 0.8. It is apparent that this phenomenon results from faster trap oxidation induced by radical reactions leading to molecular iodine formation.